THE EFFECTS OF ADVERSE CHILDHOOD EXPERIENCES (ACE) ON THE DEVELOPMENT OF DIABETES MELLITUS (DM) AND PRIMARY HYPOTHYROIDISM IN ADULTS - Alavidze , Mariam; Janjgava, Shota (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Globally, diabetes mellitus (DM) and hypothyroidism are the leading endocrine disorders. The etiology of DM and hypothyroidism is complex and the influence of toxic stress on their development is yet to be explored. Few studies report high scores of adverse childhood experiences (ACE) in DM patients. Our study aims to investigate the effect of ACE on DM, insulin resistance (IR) and primary hypothyroidism in a local population and to understand its effects on the risk of developing these diseases in adulthood. METHODOLOGY A cross-sectional web-based study was conducted. We investigated 123 adults over 21 years old who were clinically diagnosed with DM, IR and primary hypothyroidism in Georgia using an ACE (scores ranging from 0-4+) survey and the CDC guidelines for risk factors for ACE. RESULTS Analysis showed that 42 participants had only one of the three endocrine disorders: 27 with DM, 7 with IR and 8 with hypothyroidism. On the other hand, 81 patients had 2 out of 3 disorders: 27 had DM and hypothyroidism while54 had hypothyroidism with IR. ACE score of 4+ was associated with increased odds of DM (OR = 2.51, 95% CI 5.32, 1.18) and hypothyroidism (OR = 1.34, 95% CI 3.04, 0.59). The ACE was not associated with IR (OR = 0.65, 95%CI 1.34, 0.31). However, in patients with both IR and hypothyroidism, a high ACE score was observed (OR = 1.78, Cl 95% 6.28, 0.51). Participants with concomitant DM and hypothyroidism had the strongest association with ACE (OR = 3.26, 95% Cl 9.29, 1.14). CONCLUSION Results of the study suggest that a high ACE score increases the risk for DM, hypothyroidism and IR with hypothyroidism. This opens new avenues to develop preventive and management strategies for these diseases.